Transition from Critical Ontology To Metaphysical Foundations of Natural Science - De Pablo, Juan Csno (Pensamiento. Revista de Investigación e Información Filosófica, 2015)
The Critique of Pure Reason out lines an a priori ontology of nature. We find in the Critique the category of substance, which is totally a priori. However, the metaphysical principles of natural science come from the notion of matter, which is empirical. This article shows the transition carried out by Kant between two areas of knowledge. For this purpose, we will relate two Kantian texts: Prologomena to Any Future Metaphysics Which Shall Lay Claim to Being a Science and Metaphysical Foundations of Natural Science.
Keywords: newtonian physics; space; time; categories; synthetic a priori judgements; principles of understanding; movement laws; intuition; concept